International AIDS Conference in Brazil - Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2001)
In 1998, the National Coordinalion of STD/Aids returned to us lhe BID for lhe oficial presentation of Brazil to host the XV International Aids Conference, Rio 2004. At that time such proposai was presented to the National Commillee of Aids, but unfortunately there was no echo and the papers were retumed in blank. [...]